ANALISIS RISIKO KESELAMATAN DAN KESEHATAN KERJA (K3) DI LINGKUNGAN SEKOLAH DASAR DENGAN MENGGUNAKAN METODE HAZARD IDENTIFICATION RISK ASSESSMENT AND DETERMINING CONTROL (HIRADC) - Fitry Rizki Luthfiyah Kurniawan; Waspada Tedja Bhirawa; Darmawan Yulianto; Sanusi, Sungkono (Universitas Dirgantara Marsekal Suryadarma, 2025)
Occupational Health and Safety (OHS) is a crucial aspect in creating a safe and productive environment. Occupational Health and Safety (OHS) issues have traditionally focused on the industrial sector, yet schools, as venues for educational processes, also pose potential hazards that can threaten the health and safety of students. This study aims to analyze potential hazards in elementary schools using the Hazard Identification, Risk Assessment, and Determining Control (HIRADC) method. The study was conducted at MI Tazkirunnas, East Jakarta, using a quantitative descriptive approach. Data were collected through observation, interviews, and documentation of school activities and facilities. The analysis showed that 56% of areas/activities were categorized as medium risk, 25% as high risk, and 19% as low risk. The most common hazards included poorly maintained electrical installations, slippery floors, unsafe sports facilities, and the lack of emergency evacuation routes. Recommendations for control include improving physical facilities, implementing OHS SOPs, providing safety signs, and training teachers and students. These findings demonstrate the importance of implementing OHS early in schools to build a safety culture and prevent accidents.